2017
DOI: 10.1002/rmb2.12073
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical outcomes of testicular sperm extraction and intracytoplasmic sperm injection for infertile men

Abstract: PurposeTo find the best methods to achieve the highest pregnancy and birth rates for couples needing testicular sperm extraction (TESE)‐intracytoplasmic sperm injection (ICSI).MethodsRetrospectively studied were 801 patients with male factor infertility who had undergone TESE‐ICSI between April, 1996 and July, 2016 and who had been categorized into four groups: obstructive azoospermia (OA); non‐obstructive azoospermia (NOA); Klinefelter syndrome (KS); and cryptozoospermia (Crypt). The sperm retrieval rate, hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
(49 reference statements)
2
6
1
Order By: Relevance
“…Okuyama et al . 17 reported that the SRR of Japanese patients with NOA was 28.9%, which was similar to that observed in the present study. SRR was 0 for patients with AZFa, AZFb, and AZFb+c deletions in the present study; however, the number of patients analyzed was small.…”
Section: Discussionsupporting
confidence: 91%
“…Okuyama et al . 17 reported that the SRR of Japanese patients with NOA was 28.9%, which was similar to that observed in the present study. SRR was 0 for patients with AZFa, AZFb, and AZFb+c deletions in the present study; however, the number of patients analyzed was small.…”
Section: Discussionsupporting
confidence: 91%
“…In regards to the use of freshly retrieved sperm or the use of previously cryopreserved sperm from Klinefelter males, Vicdan et al feel that, in their reproductive program, "The use of fresh or cryopreserved-thawed spermatozoa on ICSI cycle outcomes are equally successful in patients with KS" (54). However, Okuyama and colleagues reported that the use of freshly harvested sperm and freshly retrieved oocytes had a significantly better pregnancy and birth rate than the use of frozen-thawed sperm and fresh oocytes, 43.2% and 28.5% compared to 33.4% and 18.7% (56). At this time, the philosophy employed by the reproductive clinicians and embryologists involved in these cases, vis-àvis fresh vs. frozen sperm, is program specific and variable.…”
Section: Adolescent or Adult Tese: Which Is The Best Choice To Maximimentioning
confidence: 99%
“…(Origio) then nitrogen vapour in a plastic freezing box (–1°C/min) Fresh testicular sperm from NOA cases (cryptozoospermic cases were also compared) 48 22 49.0 52.1 18.8 18.2 12.2 7.3 18.8 4.5 No difference in 2 PN%, CPR, LBR and IR between the two studied groups Okuyama et al . 2018 [ 35 ] Testicular sperm suspension, sperm freeze (Medi-con) then 15 min in LNV Fresh testicular sperm from NOA cases (Fresh oocytes) (OA cases and cryptozoospermic cases were also compared) 78 71 52.6 59.4 34.3 49.3 12.5 31.5 A difference in LBR in favour of the fresh sperm group Falah 2019 [ 36 ] Testicular sperm suspension, sperm freeze (FertiPro) then 15 min in LNV Fresh testicular sperm from NOA cases (OA cases were also compared) 36 32 36.0 37.0 14.3 20.0 3.6 4.0 No difference in 2 PN%, CPR and LBR between the two studied groups Zhang et al . 2021 [ 37 ] Testicular sperm suspension, sperm freezing med.…”
Section: Discussionmentioning
confidence: 99%